2012
DOI: 10.1254/jphs.12031fp
|View full text |Cite
|
Sign up to set email alerts
|

Add-On Aliskiren Elicits Stronger Renoprotection Than High-Dose Valsartan in Type 2 Diabetic KKAy Mice That Do Not Respond to Low-Dose Valsartan

Abstract: We hypothesized that aliskiren provides renoprotection in diabetic animals that did not receive sufficient renoprotection by AT1-receptor antagonist treatment. Type 2 diabetic KKAy mice were treated with group 1: vehicle or group 2: valsartan (15 mg/kg per day) from 12 to 16 weeks of age. The mice were subsequently divided into 4 groups and treated with the following combinations of drugs for another 6 weeks: 1: group 1 kept receiving vehicle, 2: group 2 continuously received 15 mg/kg per day of valsartan (Val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…The present study showed that these effects were also observed in KK-A y mice and were further exaggerated by high salt intake in type 2 diabetic KK-A y mice. In agreement with our previous studies [41,42], type 2 diabetic KK-A y mice showed renal injury characterized by glomerular podocyte injury leading to albuminuria, glomerular sclerosis and tubulointerstitial fibrosis. Similar to the effects observed on cognitive impairment and BBB disruption, these renal injuries were further aggravated by high salt intake in KK-A y mice.…”
Section: Discussionsupporting
confidence: 93%
“…The present study showed that these effects were also observed in KK-A y mice and were further exaggerated by high salt intake in type 2 diabetic KK-A y mice. In agreement with our previous studies [41,42], type 2 diabetic KK-A y mice showed renal injury characterized by glomerular podocyte injury leading to albuminuria, glomerular sclerosis and tubulointerstitial fibrosis. Similar to the effects observed on cognitive impairment and BBB disruption, these renal injuries were further aggravated by high salt intake in KK-A y mice.…”
Section: Discussionsupporting
confidence: 93%
“…Satriano et al reported that type 1 diabetic rats exhibited renal senescence with increases in p16, p21 and p27 in cortical tubules and that oxidative stress could be one of the mechanisms for proximal tubular senescence (Satriano et al, 2010). We also reported that type 2 diabetic KKAy mice exhibited renal cell senescence with increased p21 expression (Lei et al, 2012). Notably, tubular cells in the kidney of patients with early stage diabetic nephropathy were reported to be senescent (Verzola et al, 2008).…”
Section: Introductionmentioning
confidence: 90%
“…Sixty male Wistar rats were included in this study and divided randomly into four groups (15 rats each) as follows: group 1: nondiabetic control rats that received drug vehicle (normal saline); group 2: STZ-diabetic control rats that received drug vehicle (normal saline); group 3: diabetic rats treated with fenofibrate (100 mg/kg/day) suspended in 0.5% w/v of carboxymethyl cellulose [30]; group 4: diabetic rats treated with valsartan (15 mg/kg/day) dissolved in normal saline [31]. All groups were treated orally via gavage daily for 12 weeks [30].…”
Section: Methodsmentioning
confidence: 99%